Investigation on the macro-meso fatigue damage mechanism of rock joints with multiscale asperities under pre-peak cyclic shear loading. Issue 151 (December 2021) - Xu, Bin; Liu, Xinrong; Zhou, Xiaohan; Xie, Yingkun; Suliman, Lojain; Liu, Xinlin; Lin, Guangyi; Huang, Junhui
Abstract: The fatigue damage mechanical behaviours of rock joints under pre-peak cyclic shear loading are one of the key factors affecting the dynamic stability of slopes. In this study, the macro-meso fatigue damage mechanism of rock joints with multiscale asperities, when considerthe influence of the normal stress, shear rate, shear amplitude, first-order asperity angle, number of shear cycles and joint morphology, were investigated using experimental and numerical approaches under a constant normal load (CNL). The laboratory pre-peak cyclic shear experiments on the saw-tooth rock joints with different first-order asperity angles, i.e., 30°, 45° and 60°, and the same second-order asperity angle of 45°, were first conducted under different influence factors mentioned above. Six evolution stages of the shear stress with the shear displacement, i.e., initial nonlinear shear contraction deformation, approximate linear elastic shear dilation deformation, cyclic fatigue damage deformation, plastic deformation of the local compression-shear fracture, full plastic deformation of the stress brittle drop and ideal plastic flow deformation, were obtained. Additionally, the variation rules of the influence factors mentioned above with the peak (and residual) shear strengths and the cumulative shear (and normal) displacements were explored. Subsequently, the PFC 2D discrete element method was used for the meso numerical simulations, in which the meso fatigue damage evolution processes of the saw-tooth and wavy rock joints were simulated considering more number of shear cycles. Meanwhile, the change rules of the meso fatigue damage crack number (and energy) with the shear displacement (and the number of cycles), and the distribution characteristics of the meso fatigue damage particles were observed. Based on the good agreement between the macro experimental results and the meso numerical observations, the macro-meso fatigue damage failure modes of rock joints can be generally summarized as three basic types, i.e., compacting – climbing failure mode, climbing – cyclic abrading – extruding – gnawing failure mode and gnawing – sliding failure mode. Highlights: The macro-meso fatigue damage of saw-tooth rock joints with multiscale asperities under pre-peak cyclic shear is studied. The shear deformation and strength characteristics are obtained. The impact of normal stress, shear rate (amplitude), first-order asperity angle and cycle number on fatigue damage is probed. The variation rules of meso fatigue damage crack number and energy are revealed. The macro-meso fatigue damage evolution process and typical failure modes are discussed.